2013
DOI: 10.1002/hed.23468
|View full text |Cite
|
Sign up to set email alerts
|

Stomal recurrence: Salvage surgery and reconstruction utilizing microvascular free tissue transfer

Abstract: Salvage surgery using free flap reconstruction did not show improved survival rates compared with previously described techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Only a few cases using free radial forearm and anterolateral thigh flaps have been reported. 1,9 To our knowledge, one-stage pharyngoesophageal and anterior mediastinal tracheostomy reconstruction with a single skin flap has not been reported to date, and this is the first study to use a chimeric-designed anterolateral thigh flap. However, our method is only feasible when the anterolateral thigh flap has multiple cutaneous perforators that allow for splitting of the skin flap into two skin paddles.…”
Section: Discussionmentioning
confidence: 97%
“…Only a few cases using free radial forearm and anterolateral thigh flaps have been reported. 1,9 To our knowledge, one-stage pharyngoesophageal and anterior mediastinal tracheostomy reconstruction with a single skin flap has not been reported to date, and this is the first study to use a chimeric-designed anterolateral thigh flap. However, our method is only feasible when the anterolateral thigh flap has multiple cutaneous perforators that allow for splitting of the skin flap into two skin paddles.…”
Section: Discussionmentioning
confidence: 97%
“…One year survival was 40% in both groups, and only three out of eight patients with PSR Stage I–II had survivals longer than 2 years, whereas none of Sisson Stage III–IV reached such a survival time point. Sixty per cent of patients with Sisson Stage III–IV disease experienced local recurrence and eventually died [5]. Although major improvements in surgery have been applied to AMT, it has been reported that survival has not increased [5,38].…”
Section: Discussionmentioning
confidence: 99%
“…The management of airway obstruction in patients with laryngeal cancer who have not received definitive treatment is controversial [ 18 ] and there are three options to achieve an adequate airway; emergency tracheostomy, laser debulking, and emergency laryngectomy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although an emergency tracheostomy allows a biopsy and could contribute to improve the patient nutritional status before the definitive surgery, it has been reported that it constitutes a major risk factor for peristomal recurrence which presents an incidence of 5%–15% after total laryngectomy because the tumor cells may exfoliate and survive in the peristomal granulation tissue [ 18 , 19 ], and performing the laryngectomy through a previously contaminated field may increase the risk of wound infection and make difficult the construction of a definitive tracheostomy [ 19 ]. In addition, in comparison with an elective tracheostomy, the decannulation rate is lower [ 20 ].…”
Section: Discussionmentioning
confidence: 99%